Peran Guru Profesional dalam Membentuk Karakter Siswa Sekolah Dasar melalui Pendidikan Ramah Anak - Fenty Nur Aisyah; Dinda Nuriyah Syifah; Anita Imelia Sasra; Indah Anggun Munia; Ivoniar Alchani Chairun (Institut Pendidikan Indonesia, 2023)
The role of the teacher is needed to shape the character of students so that students can become good individuals. The purpose of this study is to determine the important role of professional teachers in shaping the character of elementary school students through child-friendly education. This research method uses the study literature method, namely searching for data or information by reading scientific journals and reference books related to the problem and research objectives. Based on the results of the literature study, it shows that the teacher is good at understanding the character of students, the role of the teacher is very important in shaping and developing the character of students through learning activities, habituation, school culture, extracurriculars and the school's vision and mission..